Biological markers for anxiety disorders, OCD and PTSD – a consensus statement. Part I: Neuroimaging and genetics. (3rd July 2016) - Bandelow, Borwin; Baldwin, David; Abelli, Marianna; Altamura, Carlo; Dell'Osso, Bernardo; Domschke, Katharina; Fineberg, Naomi A.; Grünblatt, Edna; Jarema, Marek; Maron, Eduard; Nutt, David; Pini, Stefano; et al.
Abstract: Objectives: Biomarkers are defined as anatomical, biochemical or physiological traits that are specific to certain disorders or syndromes. The objective of this paper is to summarise the current knowledge of biomarkers for anxiety disorders, obsessive–compulsive disorder (OCD) and post-traumatic stress disorder (PTSD). Methods: Findings in biomarker research were reviewed by a task force of international experts in the field, consisting of members of the World Federation of Societies for Biological Psychiatry Task Force on Biological Markers and of the European College of Neuropsychopharmacology Anxiety Disorders Research Network. Results: The present article (Part I) summarises findings on potential biomarkers in neuroimaging studies, including structural brain morphology, functional magnetic resonance imaging and techniques for measuring metabolic changes, including positron emission tomography and others. Furthermore, this review reports on the clinical and molecular genetic findings of family, twin, linkage, association and genome-wide association studies. Part II of the review focuses on neurochemistry, neurophysiology and neurocognition. Conclusions: Although at present, none of the putative biomarkers is sufficient and specific as a diagnostic tool, an abundance of high-quality research has accumulated that will improve our understanding of the neurobiological causes of anxiety disorders, OCD and PTSD.